DETERMINANTS OF NON-MUSLIMS INTENTION TO HAVE ISLAMIC INSURANCE PRODUCTS (International Conference on Social and Islamic Studies, 2021)
The Islamic insurance industry is developing along with the development of the Islamic finance industry. Islamic finance has universal characteristics, namely that it can not only be used by Muslims but also by non-Muslims. This study aims to examine the determinants of non-Muslim communities using sharia insurance products. This study uses quantitative research by collecting data through the distribution of questionnaires with a Likert scale to research respondents totaling 34 people. Respondents were identified as being Hinduist, Buddhist, Protestant, Catholic, and Confucian.The analysis technique used in this research is Multiple Linear Regression Analysis. The results ofthis study clearly show that premium rates, products, and promotions partially affect the intention ofnon-Muslims to use Islamic insurance products. The Islamic insurance literacy variable does not partially affect the non-Muslims intention to use Islamic insurance products. Variables Rates (Premiums), Product Quality, Promotion, and understanding simultaneously influence the intention of non-Muslims to use Islamic insurance. The non-Muslims intention to have sharia Islamic can be explained by the tarif variable, product quality variable, promotion variable, and understanding of41.4%, while the remaining 58.6% is influenced by other variables outside the variables used in this study.